2022
DOI: 10.1186/s12964-022-00836-0
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine-induced killer cells mediated pathways in the treatment of colorectal cancer

Abstract: Cytokine-induced killer (CIK) cell therapy is a type of adoptive immunotherapy that due to its high proliferation rate and anti-tumor characteristics, is being investigated to treat various solid tumors. Since advanced colorectal cancer (CRC) has high mortality and poor survival rates, and the efficacy of chemotherapy and radiotherapy is limited in treatment, the application of CIK cell therapy in CRC has been evaluated in numerous studies. This review aims to summarize the clinical studies that investigated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“… 20 , 21 In contrast, previous studies have attempted to investigate the impact of combining chemotherapy with CIK/DC-CIK cell immunotherapy in patients with mCRC, and the findings indicated that the addition of CIK/DC-CIK cells to chemotherapy significantly improved clinical outcomes compared with chemotherapy alone. 13 , 22 Our previous phase II study also found that CIK cell therapy combined with 5-fluorouridine, leucovorin and oxaliplatin (FOLFOX4) chemotherapy significantly prolonged OS when compared to the use of chemotherapy alone as an initial treatment for patients with mCRC; while the PFS was not significantly improved. 17 The current study demonstrated that PD1-T cells combined with XELOX plus bevacizumab exhibited superior efficacy in terms of PFS and OS compared to XELOX plus bevacizumab alone.…”
Section: Discussionmentioning
confidence: 98%
“… 20 , 21 In contrast, previous studies have attempted to investigate the impact of combining chemotherapy with CIK/DC-CIK cell immunotherapy in patients with mCRC, and the findings indicated that the addition of CIK/DC-CIK cells to chemotherapy significantly improved clinical outcomes compared with chemotherapy alone. 13 , 22 Our previous phase II study also found that CIK cell therapy combined with 5-fluorouridine, leucovorin and oxaliplatin (FOLFOX4) chemotherapy significantly prolonged OS when compared to the use of chemotherapy alone as an initial treatment for patients with mCRC; while the PFS was not significantly improved. 17 The current study demonstrated that PD1-T cells combined with XELOX plus bevacizumab exhibited superior efficacy in terms of PFS and OS compared to XELOX plus bevacizumab alone.…”
Section: Discussionmentioning
confidence: 98%
“…Other immune cells-based therapies have been explored due to their distinct advantages, including NK cells, 176 gamma delta T cells (γδT), 177 CD3 activated killer cells, 178 cytokine-induced killer cells (CIK), 179 dendritic cellcytokine induced killer cells (DC-CIK) 180 and lymphokineactivated killer cells. 181,182 These cell-based therapies have shown continuous progress in efficacy, specificity and reduction of side effects.…”
Section: Other Immune Cells-based Therapiesmentioning
confidence: 99%
“…These individual nucleated cells are obtained through ex vivo cultivation (11–15 days), where they undergo stimulation with various cytokines, such as anti‐CD3 monoclonal antibodies, IL‐2, and IFN‐γ, to induce their cytotoxic activity. [ 136 ] This promising immune effector cell population combines both, innate and adoptive immune responses, possessing potent antitumor activity similar to T lymphocytes and the MHC‐unrestricted tumor‐killing advantages of NK cells. [ 137 ] The immunotherapy based on CAR‐CIK has been validated in several studies.…”
Section: Off‐the‐shelf Car‐based Agentsmentioning
confidence: 99%